ANALYSIS OF TRACKING HYDRAULIC DESIGNING PROCESS - Andi Sudahan; Rusdijanto Rusdijanto; Sudjatmiko Sudjatmiko (TRANSMISI, 2019)
The use of hydraulic systems for various applications supporting work equipment is very widely used because of the nature and strength of the good and easy in its design. Hydraulic tracking can be widely applied in various needs. The principle of this work tool is designed for the release of bearings / mounting on a shaft or a ball bearing house vertically or horizontally. From the results of the hydraulic tracking planning analysis using solid works software, in this simulation to find static nodal stress (the received tensile strength) obtained the highest load is shown in the orange part of the tool with a stress value of 17.49 million N / m2, the load experienced is only 15% of the permitted maximum limit of 24,800,200,000 N / m2.then the strain that occurs in the highest value is shown on a scale with an orange of 0.03946 mm on the upper beam component, that value 1 mm means that the hydraulic frame tracking can be used properly.